AESTHETIC POSTMODERNISMIN THE NOVEL OF GENTAYANGAN PILIH SENDIRI PETUALANGAN SEPATU MERAHMU BY INTAN PARAMADITHA (ESTETIKA POSTMODERNISME DALAM NOVEL GENTAYANGAN PILIH SENDIRI PETUALANGAN SEPATU MERAHMU KARYA INTAN PARAMADITHA) - Afrodita, Meli; Zuriyati, Zuriyati; Nuruddin, Nuruddin (Universitas PGRI Sumatera Barat, 2018)
This study aims to reveal the aesthetic idiom of postmodernism in novel “Pilih Sendiri Petualangan Sepatu Merahmu” by Intan Paramaditha. This research is qualitative approach using content analysis. Data are collected by inventory textual quotes that have the aesthetic characteristics of postmodernism pastiche, parody, kitsch, camp, and schizophrenia in the novel. The research results indicatefirst, the aesthetic idiom of pastiche is indicated by duplicate of other texts as a form of author appreciation of existing literary. Second, the aesthetic idiom of parody is indicated by the presence of dialogues that make up other texts in order to criticize pre-existing texts. Thirdly, the kitsch idiom is found in the presence of confusions between high-value and high-text texts aimed at disclosing the high-value text. Fourth, the discovery of female characters who have male physical characteristics without any meaning indicates the existence of camp idiom. Fifth, the idiom of schizophrenia can be found on the whole structure of an irregular novelstory.